2021
DOI: 10.3390/d13070292
|View full text |Cite
|
Sign up to set email alerts
|

DNA Barcodes Applied to a Rapid Baseline Construction in Biodiversity Monitoring for the Conservation of Aquatic Ecosystems in the Sian Ka’an Reserve (Mexico) and Adjacent Areas

Abstract: This study is focused on the aquatic environments of the Sian Ka’an reserve, a World Heritage Site. We applied recently developed protocols for the rapid assessment of most animal taxa inhabiting any freshwater system using light traps and DNA barcodes, represented by the mitochondrial gene Cytochrome Oxidase I (COI). We DNA barcoded 1037 specimens comprising mites, crustaceans, insects, and fish larvae from 13 aquatic environments close or inside the reserve, with a success rate of 99.8%. In total, 167 barcod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 54 publications
2
3
0
Order By: Relevance
“…Most of the fish species found in this study have been reported in different aquatic systems in Yucatán and the Quintana Roo state [22,24]. Valdez Moreno et al [25], using metabarcoding in the same places as us (except Minicenote), corroborated the presence of all the species found by us in these sites [24,25]. However, we found some interesting cases, explained in the following paragraphs.…”
Section: Species Identificationsupporting
confidence: 84%
See 3 more Smart Citations
“…Most of the fish species found in this study have been reported in different aquatic systems in Yucatán and the Quintana Roo state [22,24]. Valdez Moreno et al [25], using metabarcoding in the same places as us (except Minicenote), corroborated the presence of all the species found by us in these sites [24,25]. However, we found some interesting cases, explained in the following paragraphs.…”
Section: Species Identificationsupporting
confidence: 84%
“…Although Cocalitos has the highest number of species, it is necessary to consider that this place was sampled six times compared to the others, which were visited once or twice (Table 1). Based on our results and previous studies [25], Muyil and Chuyanché lagoons have the highest number of species. The differences among the richness reported can be associated with several factors such as vegetation, shore area, and collecting method [54,56].…”
Section: Species Identificationsupporting
confidence: 83%
See 2 more Smart Citations
“…The eDNA method has been used to assess the biodiversity and distribution of medusae (Takasu et al, 2019;Ames et al, 2021). Therefore, this method is becoming a research priority, and it has great application potential in ecological monitoring and assessment (Valdez-Moreno et al, 2021;Xie et al, 2021). However, limited metabarcoding studies were conducted in the open sea with high biodiversity and complex community structure relative to coastal waters and continental shelf areas (Suter et al, 2021).…”
Section: Introductionmentioning
confidence: 99%